Pengaruh Employee Engagement Dan Work Life Balance Terhadap Job Hopping Pada Kalangan Generasi Milenial Di Kabupaten Purwakarta - Amruloh, Dedeng Abdul Gani; Yulianto, Wahyu; Wijaya, Indah Rahmah (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This research was conducted to determine the influence on Job Hopping among the millennial generation in Purwakarta Regency. In this research, the Employee Engagement and Work Life Balance variables are used as independent variables and the Job Hopping variable is the dependent variable. Primary data was collected using non-probability sampling techniques, namely sampling techniques that do not provide equal opportunities for each element or member of the population to be selected as a sample and the sample used in this research was 100 people. The data analysis method used in this research is multiple linear regression with the help of SPSS 25 software. Based on the results of research that has been carried out, it shows that partially Employee Engagement and Work Life Balance have a negative and significant effect on Job Hopping. And the entire dependent variable has a simultaneous effect on Job Hopping with a calculated F value of 25,641 with a significance level of 0.00 < 0.05. And the R square value shows a result of 0.675, which means that the entire dependent variable has a simultaneous effect of 67.5%.